(untitled) (Journal of Medical & Health Sciences Review, 2025)
Fine-needle aspiration cytology (FNAC) is a widely utilized diagnostic tool for evaluating thyroid and head-and-neck masses. Its significance lies in its minimally invasive nature, cost-effectiveness, and diagnostic accuracy. This study examines the diagnostic efficacy of FNAC in identifying thyroid malignancies and head-and-neck lesions while correlating findings with histopathological results. A retrospective analysis of 198 cases was conducted at a tertiary care centre. Patients underwent FNAC for thyroid and head-and-neck lesions, performed surgical excision and histopathological examination. FNAC results were categorized using the Bethesda System, and statistical analyses evaluated sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). FNAC demonstrated an overall sensitivity of 87.5%, specificity of 94.8%, PPV of 75.0%, and NPV of 98.3% in detecting thyroid malignancies. The Bethesda III–VI categories showed a strong correlation with malignancy risk, aligning with histopathological findings. For head-and-neck lesions, FNAC showed 91.1% accuracy in distinguishing benign from malignant cases. Reactive lymphadenitis was the most common benign diagnosis, while papillary carcinoma was the predominant malignant finding. FNAC is a valuable tool in preoperative diagnosis, enabling accurate risk stratification and aiding in clinical decision-making. Its diagnostic reliability is influenced by adherence to the Bethesda System and operator expertise. While FNAC reduces unnecessary surgeries, false negatives and atypical cytology remain limitations, warranting correlation with histopathology for definitive diagnosis. Conclusion: FNAC is a reliable, cost-effective diagnostic modality for evaluating thyroid and head-and-neck lesions. Incorporating standardized reporting systems like Bethesda enhances diagnostic precision, supporting its role as a first-line diagnostic tool in clinical practice.